The pathway to enrolling in a high-performance high school: Understanding barriers to access - Lauren Sartain; Lisa Barrow (Federal Reserve Bank of Chicago, 2020)
In 2017, Chicago Public Schools adopted an online universal application system for all high schools with the hope of providing more equitable access to highperformance schools. Despite the new system, Black students and students living in low-socioeconomic status (SES) neighborhoods remained less likely than their peers to enroll in a high-performance high school. In this paper, we characterize various constraints that students and families may face in enrolling in a highperformance high school including eligibility to programs based on prior academic achievement, distance from high-performance options, and neighborhood and elementary school resources. After adjusting for differences in these access factors, we find the gap between Black and Latinx students' likelihood of enrolling in a high-performing high school is reduced by about 80 percent. We find a similarly large reduction in the enrollment gap between students from low- and middle-SES neighborhoods after adjusting for eligibility and distance factors. These findings have implications for policies that may help equalize access to high-performance schools through changes to eligibility requirements and improved transportation options.
Keywords: 330; Bildungschancen; Nachbarschaft; Weiterführende Schule; Schulbesuch; Schwarze Menschen; Hispano-Amerikaner; USA